A Multi-Criteria Decision Analysis Framework for Prioritizing Customer Loyalty Strategies : Integrating SCM and CRM Perspective - T. Brenda Chandrawati; Erdhi Widyarto N (Soegijapranata Catholic University, 2026)
Particularly in the age of e-commerce, customer loyalty is a crucial component in assessing the viability of a firm. A Multiple-Criteria By combining the viewpoints of supply chain management and customer relationship management, a decision analysis framework is suggested to determine strategic priorities for boosting customer loyalty. 10 criteria weights and 10 alternative solutions are ranked using the Fuzzy Analytic Hierarchy Process (AHP) and TOPSIS (Fuzzy Analytic Hierarchy Process) techniques. Product availability, delivery timeliness, product/service quality, service flexibility, process efficiency, customer satisfaction, customer trust, customer engagement, service recovery, and loyalty program personalization are among the criteria employed in fuzzy AHP. Consistency is demonstrated by the pairwise comparison matrix's Consistency Ratio of 0.002. Alternative approaches to improving customer loyalty are ranked using the TOPSIS method. Service quality improvement, delivery and tracking optimization, quicker handling of complaints and returns, tiered loyalty programs, data-driven offer personalization, omnichannel customer experience, customer engagement though community and digital media, price, stock, delivery, and policy tranperancy, customer referrals, and word-of-mouth initiatives are scenarios of alternative strategies. With a closeness coefficient value of 0.611, the TOPSIS calculation techniques indicates that omnichannel customer experience is the top priority. Price,stock, delivery and, policy transperancy rank second with the closeness coefficient value of 0.601. Delivery and tracking optimization stand in third with a closeness coeficient score of 0.564. in order to improve customer loyalty, supply chain management and customer relationship managemnet must work well together, according to the results of the alternatives strategy rankings.